Dampak Wabah Corona Virus Disease Terhadap Budaya Ibadah Umat Muslim Dan Kebijakan Pemerintah - Irham, Rif’at Ayu Wijdan; Siregar, A. Khawarizmi; Jubba, Hasse (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
This paper aims to see how the response of Muslims and the government related to the Covid-19 pandemic that occurred throughout the world. This research is a qualitative study of document studies using sources consisting of publications. Muslims believe in this pandemic originating from Allah SWT, but Muslims are expected not to react to it too much and make this phenomenon to increase the capital of God for the Almighty God, Islamic jurisprudence can help find solutions to overcome it. Covid-19 Pandemic. The government as a leader in this country has implemented a policy related to the reduction of Covid-19. Many people who respond to the policies set by the government do not believe also because they oppose the government because of the lack of education by the government and Indonesian religious leaders.